La théorie des opportunités et l’erreur de généralisation - Felson, Marcus; van Dijk, Jan (Criminologie)

(untitled) (Les Presses de l'Université de Montréal, 1993)
Crime relationships are often inconsistent at different levels of aggregation for good theoretical reasons. That is why we should avoid committing the fallacy of composition, namely, drawing inferences between individuals and aggregates or from one level of aggregation to another. The routine activity approach becomes part of the solution.